2015
DOI: 10.1007/s12665-015-4533-1
|View full text |Cite
|
Sign up to set email alerts
|

Shallow and deep geothermal energy potential in low heat flow/cold climate environment: northern Québec, Canada, case study

Abstract: Northern Québec, a large and cold climate territory located north of the 49th parallel, has low average heat flow density (40 ± 9 mW/m 2 ) typical of the Canadian Shield. The lack of the thermal blanket otherwise provided by sediments in the platform of southern Québec results in deep drilling requirements for potential mining heat (80°C at some 5 km). Drilling doublet or triplet well systems at such depths into low-enthalpy granitic rocks would be expensive; however, in some cases of heat flow higher by one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Therefore, interest in assessing the potential for renewable sources to feed microgrids in remote communities has increased and several studies have been conducted (e.g., [5][6][7][8][9][10][11][12][13][14][15][16][17]). Among these options, deep geothermal energy sources can play a key role to provide baseload power and/or heat to the off-grid settlements (e.g., [18][19][20][21][22][23][24][25][26][27]). In fact, a first-order community-scale geothermal assessment undertaken in Kuujjuaq (Nunavik, Canada) suggested that the deep geothermal energy source can fulfil the community's annual average heating demand of 37 GWh [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, interest in assessing the potential for renewable sources to feed microgrids in remote communities has increased and several studies have been conducted (e.g., [5][6][7][8][9][10][11][12][13][14][15][16][17]). Among these options, deep geothermal energy sources can play a key role to provide baseload power and/or heat to the off-grid settlements (e.g., [18][19][20][21][22][23][24][25][26][27]). In fact, a first-order community-scale geothermal assessment undertaken in Kuujjuaq (Nunavik, Canada) suggested that the deep geothermal energy source can fulfil the community's annual average heating demand of 37 GWh [28].…”
Section: Introductionmentioning
confidence: 99%
“…This community is settled on the Canadian Shield, a physiographic region that has been considered a target for geothermal exploration through engineered/enhanced geothermal systems [25,29]. The feasibility of such systems has been studied in the Western Canadian Sedimentary Basin and Arctic Lands [18,19,25,[30][31][32], but few studies have been conducted in the Canadian Shield [24,25], where there are hundreds of off-grid communities relying heavily on fossil fuels [4,21]. Therefore, there is a need for a comprehensive estimation of the possible performance of deep engineered geothermal energy systems across the Canadian Shield.…”
Section: Introductionmentioning
confidence: 99%
“…Previous geothermal studies of the SLL basin in southern Québec relied on raw and/or corrected bottom-hole temperature (BHT) data obtained from oil and gas exploration wells combined with rock thermal conductivity inferred from the literature (SNC-SOQUIP, 1979; e.g. Lefebvre et Trempe, 1980;Majorowicz et Minea, 2012;Raymond et al, 2012;Majorowicz et Minea, 2015b) to estimate temperature at depth. Recent works allowed to present one-dimensional analysis of the geothermal state of the basin by defining thermal conductivity, heat generation and temperature at depth evaluated by physical measurements of thermal properties of each stratigraphic unit (Bédard et al, 2017;Nasr et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Geothermal investigations with a focus on the Canadian northern communities facing critical energy challenges have additionally been carried out (e.g., Comeau et al 2017;Giordano and Raymond 2019;Grasby et al 2013;Gunawan et al 2020;Majorowicz and Grasby 2014;Majorowicz and Minea 2015b;Minnick et al 2018). These studies indicate promising geothermal energy development for the off-grid communities due to the cold climate and the high energy cost.…”
mentioning
confidence: 99%
“…Due to the lack of heat flow data in such remote regions, it is difficult to accurately assess the extent of the geothermal resources. Majorowicz and Minea (2015b) presented an evaluation of the geothermal resources for northern Québec based on sparse heat flow data and assumptions regarding the subsurface thermophysical properties. These authors mention that a temperature of 100 °C can be reached at a depth greater than 5 km, making electricity generation difficult.…”
mentioning
confidence: 99%